Sistem Monitoring Level Ketinggian Granulation Powder Menggunakan Sensor LIDAR Berbasis Internet of Things - Purba, Jhon Hericson; Fakih Prebianto, Nanta; Raka Perdana, Alvian (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
The internet of things is defined as a technology that enables control, communication, collaboration with various hardware devices, various data, virtualizes all real things in the form of the internet and others through the internet network. In this study, a monitoring system for the height of granulated powder was created using a lidar sensor based on the internet of things which uses a measurement method via a lidar sensor. Data from the lidar sensor will be processed on the microcontroller and ethernet shield which is responsible for sending sensor data using an internet connection. Furthermore, it will be displayed on the website online. The results obtained from this simulation are tools designed to facilitate human work, reduce lost time, so that operators do not need to monitor granulation powder directly into the tank. Based on the test results and data analysis, the height of the granulated powder is directly proportional between the reference points using a measuring device with a lidar sensor or the design tool itself with a not too great difference of 4 cm or 0.022%